Hubungan antara Pendapatan, Konsumsi Energi, FDI, Perdagangan, Pariwisata, dan Lingkungan: Analisis Data 5 Negara ASEAN - Fiannurizki, Puteri Yulinda (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2024)
Climate change is still becoming a huge problem in many countries in the world including ASEAN. One of the causes is global warming due to greenhouse gas emission, including CO2. Since very few literatures discuss about the nexus of income, energy consumption, FDI, trade, tourism, and environment using panel data in ASEAN, this research tries to fill that gap. This topic needed to be studied because those variables are still pioneers for ASEAN countries to achive economy growth and development. The purpose of this paper is to estimate the impact of income, energy consumption, FDI, trade, in this case export and import, and tourism on CO2 emission. This paper uses panel data from five ASEAN countries during 1995-2014. This paper uses pooled mean group (PMG) or known as panel ARDL as method. The results show that FDI tends to increase CO2 emission, in line with Pollution Haven hypothesis. Energy consumption, export, and tourism also increase CO2 emission. Another result shows that rise of import helps decrease CO2 emission in those countries.